New methods to study macrophage biology in vitro and in vivo - Rumianek, AN (2022)
Macrophages are heterogeneous and plastic cells, which populate almost every organ in the body and migrate towards sites of inflammation. However, tools designed for studying macrophage biology, particularly genetic models and chemotaxis assays, are standardised to investigate a broad range of leukocyte populations. They fail to capture the unique properties of macrophages and distinguish them from other ontologically related populations. In this thesis, I set out to create novel in vitro and in vivo tools that are adjusted for studying macrophage biology. To address the in vivo arm of this project, I phenotyped a novel tamoxifen-inducible hCD68-CreERT2 mouse line. Having established an optimal protocol for tamoxifen dosing, I detected robust expression of Cre recombinase activity in tissue-resident macrophage populations in peritoneum, spleen and liver. Importantly, the expression was restricted to tissue-resident macrophages with marginal effects in blood leukocyte populations and splenic non-macrophage populations. When compared to other ‘macrophage-specific’ lines, hCD68-CreERT2 mice had fewer ‘off-target’ effects. Additionally, I was able to successfully use hCD68-CreERT2 mice to target macrophages present in atherosclerotic lesions. To address the in vitro arm of this project, I used the Freestyle Fluidics (FF) platform to design and optimise circuits that can be used to study macrophage migration. I created a passive diffusion-based system and an active pumping system that created stable controllable gradients. I showed that both chemotaxis and chemokinesis can be readily detected and quantified in both systems. Using the FF chemotaxis assay, I observed novel properties of macrophage behaviour such as population-level coordination of chemotaxis and the ability to sense the gradients both spatially and temporally. In summary, this project advanced the macrophage-specific technology platforms available to researchers.